Optimized hot working parameters of Fe2.5Ni2.5CrAl multi-principal element alloys - Qiao, Ling (2022)
The hot compressive deformation behavior of Co-free Fe2.5Ni2.5CrAl multi-principal element alloys (MPEAs) was investigated in the temperature and strain rate ranges of 800–1100∘C and 0.001 s−1 and 1 s−1, respectively. Microstructural observations were carried out by optical microscopy (OM) and electron backscatter diffraction (EBSD). A constitutive model based flow-stress analysis was carried out, the activation energy (Q) was obtained as 315.9 kJ/mol at steady state. The strain rate sensitivity (m), the power dissipation (η), and instability parameter (ξ) were utilized to construct the processing maps. Power-law breakdown and unstable flow occurred at the high strain rates at which strain hardening was pronounced. The optimal condition for successful hot working was determined to be at strain rates in the range of 10−2–10−3 s−1 and a temperature range of 850 ~ 1020∘C. FEM simulations revealed the strain and stress distribution during hot deformation and predicted instabilities during hot forming. The main deformation mechanism was dislocation climb with a stress exponent n > 5. The Q value for plastic flow in the power-law creep regime was calculated considering the effect of lattice diffusion of atoms and was in accordance with the measured Q value. Thus, our study revealed the hot working characteristics and the optimum processing parameters for successful hot working of Fe2.5Ni2.5CrAl MPEAs.